Anaplerotic flux into the Calvin–Benson cycle: hydrogen isotope evidence for in vivo occurrence in C3 metabolism. Issue 2 (2nd February 2022) - Wieloch, Thomas; Augusti, Angela; Schleucher, Jürgen
Summary: As the central carbon uptake pathway in photosynthetic cells, the Calvin–Benson cycle is among the most important biochemical cycles for life on Earth. A carbon flux of anaplerotic origin (i.e. through the chloroplast‐localized oxidative branch of the pentose phosphate pathway) into the Calvin–Benson cycle was proposed recently. Here, we measured intramolecular deuterium abundances in leaf starch of Helianthus annuus grown at varying ambient CO2 concentrations, C a . Additionally, we modelled deuterium fractionations expected for the anaplerotic pathway and compared modelled with measured fractionations. We report deuterium fractionation signals at H 1 and H 2 of starch glucose. Below a C a change point, these signals increase with decreasing C a consistent with modelled fractionations by anaplerotic flux. Under standard conditions ( C a  = 450 ppm corresponding to intercellular CO2 concentrations, C i, of 328 ppm), we estimate negligible anaplerotic flux. At C a  = 180 ppm ( C i  = 140 ppm), more than 10% of the glucose‐6‐phosphate entering the starch biosynthesis pathway is diverted into the anaplerotic pathway. In conclusion, we report evidence consistent with anaplerotic carbon flux into the Calvin–Benson cycle in vivo . We propose the flux may help to: maintain high levels of ribulose 1, 5‐bisphosphate under source‐limited growth conditions to facilitate photorespiratory nitrogen assimilation required to build‐up source strength; and counteract oxidative stress.